12.Solveſ K tan) ^(-1)
xdx=))
Answers
Answered by
8
Answer:
ANSWER
(1+y
2
)dx=(tan
−1
y−x)dy
dy
dx
=
1+y
2
tan
−1
y
−
1+y
2
x
dy
dx
+
1+y
2
x
=
1+y
2
tan
−1
y
Hence
IF=e
∫
1+y
2
1
.dy
=e
tan
−1
y
Hence the above differential equation changes to
e
tan
−1
y
.
dy
dx
+
1+y
2
xe
tan
−1
y
=
1+y
2
e
tan
−1
y
tan
−1
y
e
tan
−1
y
.dx+
1+y
2
xe
tan
−1
y
dy=
1+y
2
e
tan
−1
y
tan
−1
y
dy
d(e
tan
−1
y
.x)=d(e
tan
−1
y
)
Integrating both sides give us
e
tan
−1
y
.x=e
tan
−1
y
+C
Similar questions
Computer Science,
4 months ago
English,
4 months ago
India Languages,
8 months ago
Math,
1 year ago
History,
1 year ago